2012
DOI: 10.1107/s0021889812046018
|View full text |Cite
|
Sign up to set email alerts
|

{111}-specific twinning structures in nonstoichiometric ZrC0.6with ordered carbon vacancies

Abstract: Twinning structures in ordered nonstoichiometric ZrC 0.6 have been investigated experimentally and theoretically. Via transmission electron microscopy and selected area electron diffraction measurements, {111}-specific twins have been observed. Interestingly, two special types of twinning interfaces, i.e. (111) C and (111) Zr interfaces, are recognized to be formed as a result of the presence of ordered carbon vacancies. In contrast to the high stacking fault energy for twinning formation in stoichiometric ZrC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Twinning‐induced plasticity is a fundamental mechanism of the simultaneous increase in strength and ductility 20 . Although experimentally investigating on SFs and twins of HETMCs have not been reported so far, there are some experimental studies of SFs, twins, and disclocaton of unary and binary TM carbides 23,27–29 . HETMCs are known to have severe local lattice distortion (LLD); such LLD may raise the probability of SFs and nanotwins formation and influence significantly the mechanical properties of high‐entropy alloys 30–32 .…”
Section: Introductionmentioning
confidence: 99%
“…Twinning‐induced plasticity is a fundamental mechanism of the simultaneous increase in strength and ductility 20 . Although experimentally investigating on SFs and twins of HETMCs have not been reported so far, there are some experimental studies of SFs, twins, and disclocaton of unary and binary TM carbides 23,27–29 . HETMCs are known to have severe local lattice distortion (LLD); such LLD may raise the probability of SFs and nanotwins formation and influence significantly the mechanical properties of high‐entropy alloys 30–32 .…”
Section: Introductionmentioning
confidence: 99%
“…Goodman and co-workers (Goodman, 1976;Goodman & McClean, 1976) reported that the quadrupling of a H was caused by the ordering of K vacancies when x < 0.33, and the doubling of b H resulted from tiny displacements of the W atoms from the centers of the WO 6 octahedra. This kind of vacancy-ordered superlattice is often observed in non-stoichiometry compounds (Hu et al, 2013). The calculated positions of the expected reflections for the monoclinic phase are indicated by the blue bars, and indexes of XRD reflections based on both of these phases are presented in Table S1.…”
Section: Resultsmentioning
confidence: 91%
“…Recently, vacancyordered ZrC0.61 had been synthesized by spark plasma sintering and its twinning behavior was investigated [34]. Compared to the high stacking fault energy stoichiometric ZrC, the vacancyordered ZrC0.61 has substantially lower twinning energies and more available twin types [51]. Although no evidence for ordered ZrC superlattice diffractions in XRD or SAED patterns was found in this study (these techniques have also limited sensitivity to C near heavy Zr atoms), it is possible that these diffractions were very weak to be recorded; therefore, one cannot fully exclude the possibility that a vacancy-ordered ZrCx might be forming during the LBE exposure.…”
Section: Zrc/lbe Interaction Mechanismmentioning
confidence: 99%
“…8c). The presence of Al in the ZrC twin boundaries was attributed to the reduction of the twin boundary energy by the segregation of impurities such as Al and Si [51,53]. TEM investigations have indicated that Al decreases the ZrC twin boundary energy, possibly forming ternary Zr-Al-C phases by intercalating Al (or Al3C2) in the ZrC twin boundaries.…”
Section: Zrc/lbe Interaction Mechanismmentioning
confidence: 99%